2007
DOI: 10.1007/s00405-007-0264-6
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 directly influences proliferation and invasion potential of head and neck cancer cells

Abstract: Interleukin-6 (IL-6) is a multifunctional regulator of immune response and hematopoiesis. Recently, it has been reported that expression of IL-6 is correlated with prognosis in various cancer patients. In this study, we investigated whether the proliferation and invasion potential of head and neck squamous cell carcinomas (HNSCCs) were influenced by IL-6. All HNSCC cell lines, HEp-2, HSC-2, HSC-4, and SAS, were tested by reverse transcription-polymerase chain reaction (RT-PCR) and expressed the IL-6 receptor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 28 publications
1
54
1
Order By: Relevance
“…Interleukin-6 directly influences proliferation and invasion potential of head and neck cancer cells. These results suggest a direct influence of IL-6 on cell proliferation and its invasion potential as the first step of tumor metastasis (31). Expression of the MAPK extracellular signal-regulated kinase (ERK1/2) is associated with NF-κB-A Figure 5.…”
Section: Discussionmentioning
confidence: 92%
“…Interleukin-6 directly influences proliferation and invasion potential of head and neck cancer cells. These results suggest a direct influence of IL-6 on cell proliferation and its invasion potential as the first step of tumor metastasis (31). Expression of the MAPK extracellular signal-regulated kinase (ERK1/2) is associated with NF-κB-A Figure 5.…”
Section: Discussionmentioning
confidence: 92%
“…It has been suggested that IL-6 is involved in the host inflammatory reactions associated with cancer growth (39,40). There is suggestive evidence that IL-6 could play a role in tumorigenesis, but a clear understanding of the mechanisms of action is currently lacking (43). Beyond its circulating levels, there is presently an enormous scientific interest in the genes, receptors, and biological pathways involved with IL-6 (44).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies have shown that IL-6 directly influences the invasiveness of colorectal, head and neck cancers (8,9). In GBM, the autocrine regulation of IL-6 has been recognized since 1990 (10), and its aberrant expression and secretion have been found to be associated with GBM formation (11), angiogenesis, grade (12) and prognosis (13,14).…”
Section: Introductionmentioning
confidence: 99%